Effects of Tremella fuciformis Mushroom Polysaccharides on Structure, Pasting, and Thermal Properties of Chinese Chestnuts (Castanea henryi) Starch Granules under Different Freeze–Thaw Cycles - Zhuang, Weijing; Zheng, Shuyi; Chen, Feng; Gao, Shujuan; Zhong, Meifang; Zheng, Baodong (Foods, 2023)
The purpose of this study was to investigate the effect of Tremella fuciformis polysaccharides on the physicochemical properties of freeze–thawed cone chestnut starch. Various aspects, including water content, crystallinity, particle size, gelatinization, retrogradation, thermal properties, rheological properties, and texture, were examined. The results revealed that moderate freezing and thawing processes increased the retrogradation of starch; particle size, viscosity, shear type, hinning degree, and hardness decreased. After adding Tremella fuciformis polysaccharide, the particle size, relative crystallinity, and gelatinization temperature decreased, which showed solid characteristics. Consequently, the inclusion of Tremella fuciformis polysaccharide effectively countered dehydration caused by freezing and thawing, reduced viscosity, and prevented the retrogradation of frozen–thawed chestnut starch. Moreover, Tremella fuciformis polysaccharide played a significant role in enhancing the stability of the frozen–thawed chestnut starch. These findings highlight the potential benefits of incorporating Tremella fuciformis polysaccharides in starch-based products subjected to freeze–thaw cycles.